Pattern of Skin Diseases at Bahawal Victoria Hospital, Bahawalpur - Amara Amin, Sadaf Fasih, Muhammad Abdul Raziq, Abdul Ghaffar, Anila Humayun, Maryiam Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to analyze the spectrum of skin disorders in patients attending outpatient Department (OPD) of Dermatology in Bahawal Victoria Hospital, Bahawalpur. Results: A total of 1816 patients were enrolled in the study. Among the study population, infections and infestations were the most common n=1068 (59%) followed by eczemas n=450 (24.9%) and appendigeal disorders n=268 (14.6%). Conclusion: communicable skin diseases are most common and massive campaigns regarding public awareness and health reforms from the public sector are required to overcome the situation and decrease the health care burden. Keywords: Pattern, skin disorders, infections, infestations